1957
DOI: 10.1152/ajplegacy.1957.191.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Thyroid Activity of Several Strains of Mice and F1 Hybrids

Abstract: Thyroid secretion rate was determined in four strains of inbred mice and two groups of F1 hybrids. In all genotypes the thyroid secretion rate was consistently but not significantly greater in males than in females. The average thyroid secretion rates, expressed as micrograms l-thyroxine/ 100 gm body weight with the standard errors for the males and females, were: A/Jax 2.13 ± 0.12 and 1.84 ± 0.10; BALB/c 2.44 ± 0.21 and 1.84 ± 0.12; C57BR/cd 3.35 ± 0.34 and 2.45 ± 0.11; C57BL/6 4.19 ± 0.64 µg. and 3.33 ± 0.34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1960
1960
1988
1988

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Hence, thyroxine sensitivity depends strongly on the genetic background of the animals used. Perhaps it is associated with the genetic variation in endogenous thyroxine levels found across rodent strains (Amin et al, 1957;Chai, 1958).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, thyroxine sensitivity depends strongly on the genetic background of the animals used. Perhaps it is associated with the genetic variation in endogenous thyroxine levels found across rodent strains (Amin et al, 1957;Chai, 1958).…”
Section: Discussionmentioning
confidence: 99%
“…Such results may be particularly characteristic of the steroid hormones. Thyroid activity in mice has been shown to be under genetic control and the generalized activity of the strains seems to be positively correlated with the rate of thyroid me tabolism (4,23). It would be interesting to test for the existence of a somatic response factor to thyroid hormones, using activity as an index.…”
Section: S9mentioning
confidence: 99%
“…If the thyroid secretion rate is highly correlated with perslstancy of milk secretion, and it appears that it is, then it should be possible to use the thyroid secretion rate as an aid In selecting high producing animals. Work with inbred mice has indicated that the thyroid activity is under genetic control (Amin et al•, 1957) .…”
mentioning
confidence: 99%